ZAKAT COLLECTION: POTENTIAL AND REALIZATION IN BAZNAS TULUNGAGUNG REGENCY - Rafikasari, Elok Fitriani; Supriyadi, Ahmad; Yanti, Fina Indah (IAIN Tulungagung, 2021)
Zakat is one of the pillars of Islam that plays a role in handling poverty in Indonesia. The potential for zakat in Indonesia is very large, as is the case in Tulungagung regency which was collected by Baznas Tulungagung regency. The amount of potential is not yet proportional to the revenue where the total collection is still far from the existing potential. The purpose of this study was to analyze the gap between acceptance and potential from a quantitative point of view through statistical methods. The method used is the independent sample test which shows that the receipt of zakat at Baznas Tulungagung regency in 2010-2020 is far below its potential which has only reached less than 1%. The highest revenue realization was in 2018 and 2016 which only reached 0.52% of GRDP.